Keterampilan Pengucapan Kata Melalui Model Pembelajaran Cooperative Integrated Reading and Composition bagi Anak Berkesulitan Belajar - Fifi Melani Putri; Marlina Marlina (Jurnal Basicedu, 2021)
This research was motivated by the problems found by the researcher where the researcher found a child who had difficulty learning. This problem was found in SD N 34 Siguntur Tua, the child was 12 years old but was not yet fluent in reading. This study aims to prove the effect of the CIRC learning model in improving word pronunciation skills for children with learning difficulties in grade IV at SD N 34 Siguntur Tua. This type of research is experimental in the form of Single Subject Research with A-B-A design, the research subject of a child has difficulty learning with the condition that the child often adds letters and replaces letters in reading. Data collection techniques in this study using tests. The test technique is done by assigning children to read words correctly after being given intervention with the CIRC learning model. Data were analyzed using visual graph techniques. From the research that has been done, it is found that the CIRC learning model can improve the pronunciation skills of children having difficulty learning in grade IV at SD N 34 Siguntur Tua in accordance with the results of data analysis in conditions and between conditions.